PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KINERJA PADA LEMBAGA PENYIARAN PUBLIK RRI SEMARANG - M u l y a t i, M u l y a t i; Abdul Rozak, Hasan (Students Journal of Economic and Management, 2012)
This study aimed to determine the effect of work environment on job satisfaction and motivation and its impact on the performance of the public broadcaster RRI Semarang. The data in this study is primary data collected through questionnaires to the respondents at random. To determine the influence of the tool used multiple regression analysis using the t test and f test. Variable (dependent) in this study were (Y2), while the independent variables (independent) is the work environment (X1), motivation (X2), and job satisfaction (Y1). From the results of t-test showed that the work environment significant positive effect on job satisfaction, motivation significant positive effect on job satisfaction, work environment significant positive effect on performance, motivation significant positive effect on performance, job satisfaction significant positive effect on performance. F test results (test simultaneously) suggests that the work environment, motivation and job satisfaction have positive and significant with significance level a 0.05 on performance. Adjusted R Â² test results for 0324 show that the changes in performance of 32.4% was influenced by the work environment, motivation and job satisfaction, while the remaining 67.6% is due to changes in variables that do not enter in the research model.Keywords: Work Environment, Motivation, Job Satisfaction, Employee Performance